Local Tourist Food Consumption Behaviour in Kota Bharu, Kelantan / Soo-Cheng Chuah,Chai Li Cheam and Sulaika Abd. Kadir - Soo-Cheng, Chuah; Chai, Li Cheam; Abd. Kadir, Sulaika (Universiti Teknologi MARA Cawangan Kelantan, 2020)
Tourism is now one of the rapidly growing industries in the world, as well as a potential sector to generate economic development. While travelling to a locality, tourists will definitely opt for local authentic food choices to fulfil their taste buds, which provides good experience for them and adds value to their choices of destination. Food tourism has grown rapidly in recent years, especially due to the fact that local food playing an important role in differentiating a destination from another. Therefore, a tourist’s experience of tasting local food is capable of developing their perceptions and values of the place. In particular, food tourism is one of the important aspects in promoting Kota Bharu and its cultural tourism, especially for local tourists, as local food is a manifestation of the national, regional, and cultural values of a tourism destination. This study attempted to determine the explanatory factors influencing tourist food consumption in Kota Bharu, which was achieved by collecting a sample size of 236 local tourists using the convenient sampling method. The resulting findings revealed that price was a major point of concern for domestic tourists in the context of food consumption, considering the factors of gender, age, or education level accordingly. Bootstrapped multiple regression was analysed and found out that motivational and physiological factors were affecting food consumption behaviour among local tourists in Kota Bharu, Kelantan. Therefore, local food operators should take into consideration of their food prices when developing effective marketing strategies